How eliminating malaria may also prevent iron deficiency in African children - Muriuki, J; Atkinson, S (Multidisciplinary Digital Publishing Institute, 2018)
Malaria and iron deficiency are common among children living in sub-Saharan Africa. Several studies have linked a child’s iron status to their future risk of malaria infection; however, few have examined whether malaria might be a cause of iron deficiency. Approximately a quarter of African children at any one time are infected by malaria and malaria increases hepcidin and tumor necrosis factor-α concentrations leading to poor iron absorption and recycling. In support of a hypothetical link between malaria and iron deficiency, studies indicate that the prevalence of iron deficiency in children increases over a malaria season and decreases when malaria transmission is interrupted. The link between malaria and iron deficiency can be tested through the use of observational studies, randomized controlled trials and genetic epidemiology studies, each of which has its own strengths and limitations. Confirming the existence of a causal link between malaria infection and iron deficiency would readjust priorities for programs to prevent and treat iron deficiency and would demonstrate a further benefit of malaria control.